O dramático e o poético em Le concile féerique, de Jules Laforgue - Oliveira, Andressa Cristina de [UNESP] (My University, 2010)
We briefl y present here a dramatic work of the French Symbolist poet Jules Laforgue – Le Concile Féerique. During the analysis, we see collages of Fleurs de bonne volonté poems, conceived in a dialogued and original way, showing us, mostly, in the work of the French poet, the modernity and the persistence of poetry.

Apresenta-se, aqui, brevemente, uma obra dramática do poeta simbolista francês Jules Laforgue intitulada Le Concile Féerique. Ao longo da análise, vêem-se colagens de poemas de Fleurs de Bonne Volonté, realizadas em forma dialogada e de maneira original, destacando-se, sobretudo, na obra do francês, a modernidade e a persistência da poesia.
The dramatic and the poetic in Le Concile Féerique by Jules Laforgue
Keywords: Laforgue; French Symbolism; Dramatic works; Poetry; Originality; Laforgue; Simbolismo francês; Teatro; Poesia; Originalidade